СРАВНИТЕЛЬНАЯ ХАРАКТЕРИСТИКА ИЗДАНИЙ РОМАННОГО ТВОРЧЕСТВА МИР ДЖАЛАЛА - Гусейнова Айтен Казанфар кызы (World Science, 2018)
In the article, the author of advanced ideas, explores published copies of novelist Mir Jalal's novels "The Resurrection Man (1936)", "The Open Book (1945)", "People of the Same Age,1948", "The New City (1951)", "Where are we going” (1957) comparative analysis. The repeated publication of the novels of the Soviet in the Soviet era or in the modern era, always proves the relevance of the talented creator. Two of the five novels of Mir Jalal, the one we talked about, have been the subject of past and the third one.